Toward clean manufacturing: an analysis and validation of a modified Johnson–Cook material model for low and high-speed orthogonal machining of low-carbon aluminum alloy (Al 6061-T6) - Akram, Sohail; Jaffery, Syed Husain Imran; Anwar, Zahid; Khan, Mushtaq; Khan, Muhammad Ali (International journal of advanced manufacturing technology, 2023)
In this research, sustainable machining of the aluminum alloy (Al 6061-T6) is considered. Aluminum is a durable and infinitely recyclable material as well as light in density, causing no environmental effects in comparison with other materials including steel or plastic. Currently, due to a lack of understanding and inefficient application of modern sustainable manufacturing tools and technologies, around 20% of the investment made in metal cutting tools was reported to have been wasted. The constitutive law describing the thermo-mechanical behavior of workpiece material significantly affects the success of any finite element modeling (FEM). Different values of Johnson–Cook (JC) material constants determined through different methods are found in the literature which consequently affects the predicted results. Current research used an inverse methodology to determine the JC material constants and compare them with published literature. The proposed JC material model was then verified through orthogonal machining of Al 6061-T6 alloy at different machining conditions. Cutting forces at high-speed machining were found to decrease remarkably due to adiabatic heating conditions and short contact time between the workpiece and tool material. The JC material constants determined through the current approach produced better predictions of the cutting forces at high-speed machining conditions suitable for sustainable manufacturing.